Impacts of gait biomechanics of patients with thoracolumbar kyphosis secondary to Scheuermann’s disease - Cheng, Hao; Jiang, Zi-Ang; Chen, Liang; Wang, Guo-Dong; Liu, Xiao-Yang; Sun, Jian-Min; Tsai, Tsung-Yuan (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Thoracolumbar kyphosis (TLK) is a common feature in patients with spinal deformities. However, due to limited studies, the impacts of TLK on gait have not been reported. The objective of the study was to quantify and evaluate the impacts of gait biomechanics of patients with TLK secondary to Scheuermann’s disease. Methods: Twenty cases of Scheuermann’s disease patients with TLK and twenty cases of asymptomatic participants were recruited into this study. And the gait motion analysis was conducted. Results: The stride length was shorter in the TLK group compared to control group (1.24 ± 0.11 m vs. 1.36 ± 0.21 m, p = 0.04). Compared to control group, the stride time and step time were more prolonged in the TLK group (1.18 ± 0.11s vs. 1.11 ± 0.08 s, p = 0.03; 0.59 ± 0.06 s vs. 0.56 ± 0.04 s, p = 0.04). The gait speed of the TLK group was significantly slower than it of control group (1.05 ± 0.12 m/s vs. 1.17 ± 0.14 m/s, p = 0.01); In the sagittal plane, the range of motion (ROM) of the hip in the TLK group was significantly smaller than that of the control group (37.71 ± 4.35° vs. 40.05 ± 3.71°, p = 0.00). In the transverse plane, the adduction/abduction ROMs of the knee and ankle, as well as the internal and external rotation of the knee, were smaller in TLK group than ROMs in the control group (4.66 ± 2.21° vs. 5.61 ± 1.82°, p = 0.00; 11.48 ± 3.97° vs. 13.16 ± 5.6°, p = 0.02; 9.00 ± 5.14° vs. 12.95 ± 5.78°, p = 0.00). Discussion: The main finding of this study was that measurements of gait patterns and joint movement of the TLK group were significantly lower than those of the control group. And these impacts have the potential to exacerbate degenerative progress of joints in the lower extremities. These abnormal features of gait can also serve as a guideline for physicians to focus on TLK in these patients.